Deoxygenation of Exfoliated Graphite Oxide under Alkaline Conditions: A Green Route to Graphene Preparation - Fan, Xiaobin; Peng, Wenchao; Li, Yang; Li, Xianyu; Wang, Shulan; Zhang, Guoliang; Zhang, Fengbao (Advanced materials (Weinheim), 2008)
Stable graphene suspensions are prepared using a new, green, and intriguing synthetic route. Graphene can be directly prepared by the fast deoxygenation of exfoliated graphite oxide in strong alkaline solutions at low temperatures (50–90 °C), in the absence of reducing agents. This study opens an opportunity towards the production of processable graphene on an industrial scale.